#### Answer

$w' = 21z^{6}-21z^{2}+42z^{1}$
$w'' = 126z^{5}- 42z+42$

#### Work Step by Step

$w = 3z^{7}-7z^{3}+21z^{2}$
$w' = 21z^{7-1}-21z^{3-1}+42z^{2-1}$
$w' = 21z^{6}-21z^{2}+42z^{1}$
$w'' = 126z^{6-1}- 42z^{1}+42$
$w'' = 126z^{5}- 42z+42$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$w' = 21z^{6}-21z^{2}+42z^{1}$
$w'' = 126z^{5}- 42z+42$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.